PEREMEJAAN KARET RAKYATSEBAGAI SOLUSI PENINGKATAN PRODUKTIVITAS KARET (STUDI KASUS DI PROPINSI JAMBI) - Rina Astarika (Universitas Batanghari Jambi, 2015)
Jambi province is the third largest rubber producer in Indonesia. Commodities play an important role in the economy in all the districts in Jambi province. The area of rubber plantations in Jambi province has reached 567 042 ha, with the result by 312 925 tonnes of processed rubber. Condition of the rubber plantation area consist of a 105 566 ha are crops produced (TM), 330 820 ha are immature plants and 130. 656 Ha is old and damaged crops. This condition causes a low level of productivity of rubber lands an average of only 714 kg / ha / yr, therefore the need for rejuvenation of the rubber in Jambi was given the top priority for the government and society.Some problems were found in the rejuvenation of the rubber farmers' lack of knowledge and technology, lack of readiness of farmers and farmer groups, the readiness of funds, lack of guidance counselors, and support of the banks that have not been optimal.In order to program a maximum rejuvenation of the rubber can be done should be done in the application of rubber cultivation technology is good and true suggestions that will improve the productivity of rubber plantations in the long run, as well as the necessary cooperation between the Plantation Office, research institutes, BPN, Banking, and Bapelluh Bakorluh, and all stakeholders related facilities as a provider of technology transfer, financing institutions, and institutions so that the next provider of production facilities is expected to rubber in Jambi rejuvenation program can be run in accordance with success. Hopefully!Keywords: replanting rubber, improved productivity of rubber